Etiologies et pronostic des occlusions intestinales aigues mécaniques à l’Hôpital National de Zinder: étude transversale sur 171 patients - Adamou, Harissou (Pan Afr Med J, 2016)
Acute mechanical intestinal obstruction (AIO) is one of the most frequent pathologies in emergency digestive surgery. The objective of this study was to describe the etiologic and prognostic features of acute mechanical intestinal obstruction at the National Hospital of Zinder (HNZ), Niger. We conducted a cross-sectional study including all the patients operated for AIO over a period of 24 months (January 2013 - December 2014) Mechanical intestinal obstructions represent 24.50% (n=171) of digestive surgical emergencies (n=622). The median age was 25 years (range: 1 day-95 years). The sex ratio was 3.5 in favour of men. Children accounted for 38.60% (n=66). The seat of the obstacle was at the level of the small bowel in 60.82% (n=104), colonic in 21.63% (n=37) and mixed in 17.54% (n=30). The mechanism of strangulation accounted for 88,89% (n=152), among these strangulated hernias were detected in 49,70% (n=85) of patients and acute intestinal invaginations in 19,88% (n=34) of patients. Anorectal malformations and tumors were the main cause of obstruction in 7.02% (n=12) and 3.51% (n=6) of cases respectively. Intestinal resection was performed in 52 cases (30.41%). Septic complications prevailed (n=39/53); among these parietal suppuration (n=23). The average length of stay in hospital was 7.82 days. The overall mortality rate was 11.70% (n=20). This was statistically correlated to intestinal necrosis (p=0.01) and to delayed hospital admission (p=0.04). There are many causes of AIO which are dominated by strangulated hernia. The high morbidity and mortality rate from AIO might be prevented by early treatment performed before intestinal necrosis occurs.